Comparative Study of Chemical Composition and Biological Activity of Yellow, Green, Brown, and Red Brazilian Propolis. (21st July 2016) - Machado, Christiane Schineider; Mokochinski, João Benhur; Lira, Tatiana Onofre de; de Oliveira, Fátima de Cassia Evangelista; Cardoso, Magda Vieira; Ferreira, Roseane Guimarães; Sawaya, Alexandra Christine Helena Frankland; Ferreira, Antonio Gilberto; Pessoa, Cláudia; Cuesta-Rubio, Osmany; Monteiro, Marta Chagas; de Campos, Mônica Soares; et al.
Abstract : The chemical composition and biological activity of a sample of yellow propolis from Mato Grosso do Sul, Brazil (EEP-Y MS), were investigated for the first time and compared with green, brown, and red types of Brazilian propolis and with a sample of yellow propolis from Cuba. Overall, EEP-Y MS had different qualitative chemical profiles, as well as different cytotoxic and antimicrobial activities when compared to the other types of propolis assessed in this study and it is a different chemotype of Brazilian propolis. Absence of phenolic compounds and the presence of mixtures of aliphatic compounds in yellow propolis were determined by analysing 1 H-NMR spectra and fifteen terpenes were identified by GC-MS. EEP-Y MS showed cytotoxic activity against human tumour strain OVCAR-8 but was not active against Gram-negative or Gram-positive bacteria. Our results confirm the difficulty of establishing a uniform quality standard for propolis from diverse geographical origins. The most appropriate pharmacological applications of yellow types of propolis must be further investigated.